Advancing Obsessive–Compulsive Disorder Research: Insights from Transgenic Animal Models and Innovative Therapies - Xinyuejia Huang; Linglong Xiao; Mengqi Wang; Yang Wu; Hao Deng; Wei Wang (Brain Sciences)
Obsessive–compulsive disorder (OCD) is a prevalent, chronic, and severe neuropsychiatric disorder that leads to illness-related disability. Despite the availability of several treatments, many OCD patients respond inadequately, because the underlying neural mechanisms remain unclear, necessitating the establishment of many animal models, particularly mouse models, to elucidate disease mechanisms and therapeutic strategies better. Although the development of animal models is ongoing, there remain many comprehensive summaries and updates in recent research, hampering efforts to develop novel treatments and enhance existing interventions. This review summarizes the phenotypes of several commonly used models and mechanistic insights from transgenic models of OCD, such as knockout mouse models. In addition, we present the advantages and limitations of these models and discuss their future in helping further understand the pathophysiology and advanced treatment. Here, we highlight current frontline treatment approaches for OCD, including neuromodulation and surgical interventions, and propose potential future directions. By studying gene mutations and observing phenotypes from available OCD animal models, researchers have classified the molecular signatures of each model reminiscent of changes in brain areas and neural pathways, with the hope of guiding the future selection of the most appropriate models for specific research in the OCD field.